Comportements et pratiques écologiques des étudiants : retours d’expérience dans une résidence étudiante « all-inclusive » en conteneurs - Alexis Alamel; Catalina Santana Bucio (Développement Durable et Territoires)
The student housing sector has faced major challenges. On the one hand, it requires constructing housing that is environmentally friendly. On the other hand, there is a need to promptly respond to the needs and demands of student housing. The A’Docks hall of residence, built in 2010 from shipping containers, was particularly denounced in the media. This paper shows the results of a survey, using mixed-methodology, conducted for the student residents to understand the effects of their energy consumption behaviours and their recycling habits on their residential quality of life. The results show a heightened level of ecological appreciation and diverse eco-responsible practices but these are limited by constraints in housing construction and issues tied to the residence’s management.